Understanding the Decline in the Price of Oil since June 2014 - Christiane Baumeister; Lutz Kilian (Center for Economic Studies and ifo Institute (CESifo), 2016)
Some observers have conjectured that the steep decline in the price of oil between June and December 2014 resulted from positive oil supply shocks in the second half of 2014. Others have suggested that a major shock to oil price expectations occurred when in late November 2014 OPEC announced that it would maintain current production levels despite the steady increase in non-OPEC oil production. Both conjectures are perfectly reasonable ex ante, yet we provide quantitative evidence that neither explanation appears supported by the data. We show that more than half of the decline in the price of oil was predictable in real time as of June 2014. We attribute 11 of this predictable decline to the cumulative effects of adverse demand shocks prior to July 2014, reflecting a slowing global economy, and 16 to positive oil supply shocks and to shocks to expected oil production that occurred prior to July 2014. The remaining oil price decline is accounted for by a shock to oil price expectations in July 2014 that lowered the demand for oil inventories and a shock to the demand for oil associated with an unexpectedly weakening economy in December 2014, which lowered the price of oil by an additional 9 and 13, respectively.
Keywords: Q43; C53; 330; oil price declines; OPEC; oil supply; oil demand; shale oil